An analytical study of Malaysia’s quality of life indicators - Md. Dali, Norimah; Ahmad Sarkawi, Azila; Abdullah, Alias (2017)
Abstract: In Malaysia, there are several set of indicators used to measure quality of life vis-à-vis liveability of cities. Three remarkable set of indicators are the Malaysian Wellbeing Index (2 sub composites, 14 components, 68 indicators), the Malaysian Urban Rural National Indicators for Sustainable Development (6 dimensions, 21 themes, 36 indicators) and the Malaysian Family Wellbeing Index (7 domains, 24 indicators). They are governed by government agencies of Economic Planning Unit (EPU), Federal Town and Country Planning Department (FTCPD) and National Population and Family Development Board (NPFDB) respectively. Quality of life is directly related to liveability and the latter is very much influenced by the fulfillment of the need for self-fulfilment — physical, social, emotional and spiritual. In the Malaysian context quality of life is interchangeably used to mean liveability, sustainability, wellbeing and happiness in its towns and cities. The study employed meta-ethnography qualitative approach by in-depth analysis and synthesis on the respective set of indicators. It is a systematic approach that enables comparison, analysis and interpretations to be made that can inform theorizing and practice. The analysis revealed the commonalities and differences amongst the three set of Malaysia’s quality of life indicators. Noticeably, religion and spirituality become one of the concerns. For town planners and city managers, the result indicates the state of people living condition in cities that influence planning and development in the long run. Overall, the indicators used are quite varied suiting their organisation’s aim and objectives but they are sharing the common themes of politics, economics, social, environment and infrastructure. Key words: Malaysia; quality of life; liveability; wellbeing; index JEL codes: H